Individual Consequences of Occupational Decline - Per-Anders Edin; Tiernan Evans; Georg Graetz; Sofia Hernnäs; Guy Michaels (Center for Economic Studies and ifo Institute (CESifo), 2019)
What are the earnings and employment losses that workers suffer when demand for their occupations declines? To answer this question we combine forecasts on occupational employment changes, which allow us to identify unanticipated declines; administrative data on the population of Swedish workers, spanning several decades; and a highly detailed occupational classification. We find that, compared to similar workers, those facing occupational decline lost about 2-5 percent of mean cumulative earnings from 1986-2013. But workers at the bottom of their occupations' initial earnings distributions suffered considerably larger losses. These earnings losses are partly accounted for by reduced employment, and increased unemployment and retraining.
Keywords: O33; J24; J62; 330; technological change; occupations; inequality